A systematic surgical approach to hepatoblastoma with intracardiac extension. (May 2017) - Sayed, Sajid; Prabhu, Sudesh; Fawcett, Jonathan; Choo, Kelvin; Alphonso, Nelson
Hepatoblastoma is very uncommon in children, and intracardiac extension is rare. The SIOPEL-4 regime for metastatic hepatoblastoma has extended the surgical options with good results. We successfully treated a boy aged 2 years and 9 months with hepatoblastoma, using a multidisciplinary surgical strategy involving an extended left hepatectomy, left adrenalectomy, biopsy of the paraaortic and coeliac lymph nodes, and resection of the inferior vena caval-right atrial extension of the hepatoblastoma, under cardiopulmonary bypass and deep hypothermia.